Evaluation of rice breeding lines containing root QTLs under different water management environments - Deshmukh, Vivek; Kamoshita, Akihiko; Amézquita, Nelson; Espinosa, Natalia; Ogawa, Satoshi; Kitomi, Yuka; Uga, Yusaku (2024)
Investigating effects of introgressed root-trait QTLs in field environments is a challenging task. Seven rice BC3F4 lines with at least one of six QTLs for root vertical distribution (DRO1, DRO2, DRO3, qFSR4, qRL6.1, QRO2) introgressed into a popular Colombian variety, FEDEARROZ 60, were evaluated for changes in root traits together with a BC3F4 line lacking root QTLs and the parent FEDEARROZ 60. A flooded experiment with deep-flooded and shallow-flooded treatments and an aerobic experiment using a raised-bed system were repeated in two seasons in Central Colombia. In the flooded experiment, ST604_302, containing DRO2, showed the highest root weight and root weight proportion in the 20–30-cm soil layer. The average root weight and proportion of roots at the 10–20-cm soil depth and average root weight at the 20–30-cm depth were significantly greater for the lines containing DRO2 than for those without. In the aerobic experiment, the four lines with DRO2 had higher deep-root ratios than the other genotypes. In the aerobic experiment, a higher deep-root ratio did not lead to greater root weight at either depth examined; the root weight parameters showed genotype × season interaction, and genotype had no significant effect on root weight. In the flooded experiment, the four DRO2-introgressed lines showed higher root length density below 10-cm depth than other lines in the deep-flooded treatment but not in the shallow-flooded treatment. These results showed limited but positive changes in deep-root growth in field environments through root-QTL introgression, and revealed interactions with water management and season.